BARRIERS OF IMPLEMENTING BUILDING INFORMATION MODELLING (BIM) IN QUANTITY SURVEYING CONSULTANT’S FIRM IN MALAYSIAN’S NORTHERN’S REGION - Nur Syafiah Mohd Yunus; Mohamad Tajudin Saidin; Fairiz Miza Yop Zain; Mohd Firdaus Zainuddin; Edelin Hussein (Journal of Islamic, Social, Economics and Development, 2023)
Malaysian construction industry plays a crucial part in creating national wealth. In achieving the dream of a well-developed country reputation, technologies and innovation need to be adopted in the industry for Malaysia to readily set in motion for the fourth industrial revolution 4.0. Building Information Modelling (BIM) as one of the processes, supported by various tools, plays a vital role in enhancing the construction projects as well as ease the works for the industry players. Quantity surveyors shall be one of the construction teams to implement the technologies in enhancing their estimating and cost planning game. However, various challenges and barriers preventing the firms to truly apply the innovation. Moreover, the northern’s region of Malaysia indicates the lowest application of the software in the firms bring about to this research to take place. The objective of this study is to determine the barriers of BIM implementation in the quantity surveying consultant firms in northern’s region. The outcome gained from the distribution of the questionnaire via the 22 respondents of the quantity surveying firms indicates the top two barriers for the BIM implementation were high cost to operate software and high cost of BIM training. Therefore, based on the findings, the government shall give incentives to encourage QS consultants to invest in BIM.